Interdisciplinary research methodology: foundations and projections - Llanos Ceballos, Adolfo León (2022)
The article examines the formulation of an interdisciplinary research methodology for tertiary education. The parceled vision of knowledge through the teaching, learning and evaluation of subjects that correspond to disciplines have become scarce, given that the challenges facing the protection of the planet and the defense of human life, demand the implementation of a holistic perspective, which moves away from the compartmentalization of knowledge. The document, by means of a systematization method, in its first part, addresses three categories whose key purpose is to support the proposal, which are: the university, knowledge and territory. In the second part, two substantial components of the discipline are disaggregated, on the one hand, the methods, in their double aspect ―normative and gnoseological―, and on the other hand, the concepts, in their epistemological structure. Next, the interdisciplinary fields are presented, understood as the spaces for the construction of the interdiscipline that includes objects of study, tensions, and above all, needs. As a result, an exercise on the automation of coriander cultivation is outlined. It is concluded that this type of research is feasible, and the university, as a sociocultural system where scientific knowledge is built, should be oriented towards interdisciplinary knowledge.